Letting it go - Katin, Miriam (Drawn & Quarterly, 2013)
A Holocaust survivor and mother, Katin's world is turned upside down by the news that her adult son is moving to Berlin, a city she's villainized for the past forty years. As she struggles to accept her son's decision, she visits the city twice, first to see her son and then to attend a museum gala featuring her own artwork. What she witnesses firsthand is a city coming to terms with its traumatic past, much as Katin is herself.